2023
DOI: 10.3389/fphar.2022.1035220
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the neuroprotective and anti-neuroinflammatory effects and mechanisms of Moringa oleifera

Abstract: Neurodegenerative diseases (NDs) are sporadic maladies that affect patients’ lives with progressive neurological disabilities and reduced quality of life. Neuroinflammation and oxidative reaction are among the pivotal factors for neurodegenerative conditions, contributing to the progression of NDs, such as Parkinson’s disease (PD), Alzheimer’s disease (AD), multiple sclerosis (MS) and Huntington’s disease (HD). Management of NDs is still less than optimum due to its wide range of causative factors and influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 190 publications
0
8
0
Order By: Relevance
“…There is increasing support for the use of some herbal medicines, nutraceuticals, plant extracts and supplements as alternative therapeutic options for the treatment of Alzheimer’s disease [ 17 , 18 ]. Numerous phytochemicals found within these alternative treatments fit the bill as potential AD therapeutics for a number of reasons [ 14 , 15 , 16 , 17 , 18 ]. First, they target specific, critical components (e.g., BACE1, Aβ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing support for the use of some herbal medicines, nutraceuticals, plant extracts and supplements as alternative therapeutic options for the treatment of Alzheimer’s disease [ 17 , 18 ]. Numerous phytochemicals found within these alternative treatments fit the bill as potential AD therapeutics for a number of reasons [ 14 , 15 , 16 , 17 , 18 ]. First, they target specific, critical components (e.g., BACE1, Aβ).…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that some herbal medicines, nutraceuticals and supplements may provide alternative therapeutic options with reduced risk of side effects for a diversity of diseases, including Alzheimer’s [ 14 , 15 , 16 , 17 , 18 ]. Nutraceuticals or biopharmaceuticals are foods with proven or purported medical effects while herbal medicines are medicines specifically made from plants [ 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the enhancement of the cellular antioxidant defense system, MIC demonstrate a capacity to prevent oxidative damage to neurons, contributing to overall neuroprotection [ 8 ]. In parallel to PEITC, MIC exhibit anti-inflammatory effects by suppressing the production of inflammatory cytokines and mediators in the brain [ 101 , 102 ]. Notably, a study conducted by Onasanwo and colleagues observed the potential pharmacological role of Moringa oleifera isothiocyanates in preventing the loss of neuronal cells and managing Alzheimer’s disease.…”
Section: Neuroprotective Properties Of Isothiocyanatesmentioning
confidence: 99%
“…Wedelia chinensis, also referred to as "Pilabhamgara" or "Bhringraj," is a perennial herb in the Asteraceae family [9][10]. The plant is scientifically reported to possess antioxidant, antiseptic and antimicrobial properties [10][11][12]. Coccinia is a climber-type plant and belongs to the family Cucurbitaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Coccinia is a climber-type plant and belongs to the family Cucurbitaceae. It's a great source of flavonoids, terpenoids, glycosides and tannins, among other classes of bioactive natural compounds [11][12][13]. Numerous antifungal properties of selected plant extracts such as Azadirachta indica, Lantana camara, Moringa oleifera, Wedelia chinensis and Coccinia grandis have outstanding antifungal properties [14][15][16][17][18][19] as well as other numerous properties have been studied [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%